Home tweet home - Mad Halid, Norhidayah (Universiti Putra Malaysia Press, 2015)
In the natural environment, birds need a nest for their settlement. Nests are made to protect the eggs and young from the threat of predators and weather. In fact, the parent birds feed and raise their children in the nest. The task of collecting the materials and build a nest is usually done in pairs. However, there are also birds that build their nests in groups. There are various types of nest such as cavity, pendulum, cup, platform, and sphere. The shapes that are built depends on their behavior.